DIGITAL INNOVATION IN AUTOMOTIVE EDUCATION : IMPROVING COLLABORATION SKILL OF STUDENT USING INTERACTIVE FLIPBOOK - Kunesa, Faisal Anas; Warju, Warju; Wailanduw, A. Grummy; Nur, Hamid Ramadhan (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Students in the twenty-first century need to be able to work together effectively and be actively involved in their own education. Creating interactive learning material based on flipbooks is one way to bolster these abilities. The purpose of this research is to investigate how students' collaborative abilities are impacted by the use of flipbook media and to document their reactions to the created materials. The researchers in this study used a quasi experimental (group posstest design), which meant that only one set of students received the instructional materials (flipbooks) and the associated activities. An observation sheet for teamwork abilities and a questionnaire for student feedback made up the study tools. After using flipbook media, students cooperation abilities significantly improved, as shown by a significance value of 0.000 < 0.05 in the comparative test on collaboration skills. In addition, the reliability test yielded a Cronbach's Alpha score of 0.846, reflecting strong reliability, and the validity test showed that all ten questionnaire questions had correlation coefficients higher than 0.361, proving that all items were valid. Evident from these results, the flipbook medium was well-received by the student. Thus, the created flipbook-based learning material is well-received and useful for improving students teamwork abilities and receives positive responses, making it suitable for use as an interactive learning medium in twenty-first century learning.   ABSTRAK Siswa di abad ke-21 perlu mampu bekerja sama secara efektif dan terlibat aktif dalam pendidikan mereka sendiri. Membuat materi pembelajaran interaktif berbasis flipbook adalah salah satu cara untuk meningkatkan kemampuan ini. Tujuan penelitian ini adalah untuk menyelidiki bagaimana kemampuan kolaborasi siswa dipengaruhi oleh penggunaan media flipbook dan untuk mendokumentasikan reaksi mereka terhadap materi yang dibuat. Para peneliti dalam studi ini menggunakan desain kuasi eksperimental (desain posttest kelompok), yang berarti hanya satu kelompok siswa yang menerima materi pembelajaran (flipbook) dan aktivitas terkait. Lembar observasi untuk kemampuan kerja tim dan kuesioner untuk umpan balik siswa merupakan alat penelitian. Setelah menggunakan media flipbook, kemampuan kerja sama siswa meningkat secara signifikan, seperti yang ditunjukkan oleh nilai signifikansi 0,000 < 0,05 dalam uji komparatif pada keterampilan kolaborasi. Selain itu, uji reliabilitas menghasilkan skor Alpha Cronbach sebesar 0,846, yang mencerminkan reliabilitas yang kuat, dan uji validitas menunjukkan bahwa semua sepuluh pertanyaan kuesioner memiliki koefisien korelasi lebih tinggi dari 0,361, membuktikan bahwa semua item valid. Terbukti dari hasil ini, media flipbook diterima dengan baik oleh siswa. Dengan demikian, materi pembelajaran berbasis flipbook yang dibuat diterima dengan baik dan bermanfaat untuk meningkatkan kemampuan kerja tim siswa serta mendapat respons positif, sehingga cocok digunakan sebagai media pembelajaran interaktif dalam pembelajaran abad ke-21.